Li0.7NbS2: structural effects of increased alkali metal content - Salyer, P; Barker, MG; Gregory, D; Jones, M; Wilson, C (2003)
Crystals of lithium niobium disulfide [LiyNbS2; y = 0.70 (9)] have been prepared by separated reactants metathesis (SRM) at 1073 K. Single-crystal data collected at reduced temperature [150 (2) K] indicate that the compound is isostructural with Li0.63NbS2 [Salyer, Barker, Blake, Gregory and Wilson (2003). Acta Cryst. C59, i4-i6], crystallizing in the hexagonal space group P63/mmc (No. 194). Li 0.7NbS2 shows an expansion of both the a and c lattice parameters when compared with previously reported results on Li yNbS2 intercalation compounds with y < 0.70. This provides the first single-crystal structural evidence of unit cell expansion with increasing lithium content in LiyNbS2, where y > 0.5. κ 2003 International Union of Crystallography Printed in Great Britain - all rights reserved.